Percepción ambiental en dos comunidades cubanas - Borroto Pérez, María; Rodríguez Pérez, Lucas; Reyes Ramírez, Aurelio; López Vázquez, Blanca Alejandra (M+A. Revista Electrónica de Medioambiente, 2011)
A considerable part of our newspaper acting depends on the capacity to perceive the different elements that conform the means in which unwrap ourselves, our environmental perceptions appropriately they condition the attitudes, sensibilities, and they influence considerably in the orientation and regulation of our actions toward the environment; it is for it that is important the study of this process, by way of to contribute to that the human development is adapted and harmonious, according to the characteristics of the environment that obtain a coherent behavior with the pattern of the sustainable. As part of an investigative project the environmental perception of the members of the communities was evaluated organized in four goal groups. It was designed and it validated for experts a questionnaire and four variables to use it of base in surveys to the population of this communities. They were considered the variable environmental vision, environmental responsibility, environmental attitude and decision to incorporate to the change and vision on the environmental preparation. The environmental perception was diagnosed of each one of the groups goal in the two communities, finding the evaluated better variable the formation, followed by the attitude and environmental vision. This will allow the design and implementation of a strategy in the context for the environmental education and with it knowledge, attitudes and consequent environmental behavior with the sustainable pattern of development.